“Simba yagongwa”: metaphors in soccer reporting headlines in Tanzania’s Uhuru Swahili daily - Gastor Cosmas Mapunda (Cogent Arts & Humanities)
This paper attempts a linguistic analysis of metaphor use in the Tanzanian Swahili Uhuru daily headlines that report soccer events. We purposively and conveniently chose 35 headlines published in 1960s–2020s to examine metaphor use in the newspaper as a way of attracting readership and interest. We addressed four objectives, namely (i) explaining how the use of metaphors in soccer reporting headlines has evolved over time; (ii) establishing a typology of metaphors used in the headlines; (iii) explaining the source of their metaphoricity; and (iv) discussing the linguistic features of the metaphors. The study was guided by the Conceptual Metaphor Theory. Findings suggest that some metaphors used in the early decades were marked for tense and aspect, as opposed to those used in later decades. Also, the metaphors can be classified as fight metaphors, war metaphors, destruction metaphors, daily activities metaphors, and miscellaneous domain metaphors. Their metaphoricity comes from associating linguistic items with domains such as animal names, farming, topography, and slang expressions. Verbs formed the most popular category. The study’s significance is that metaphors carry cultural information, are persuasive, and arouse readers’ interest. They can also be helpful to learners of Swahili.